Circulation of bovine viral diarrhea virus – 1 (BVDV-1) in dairy cattle and buffalo farms in Ismailia Province, Egypt - Mohamed Ahmed Soltan; Rebecca P Wilkes; Mohamed Nagy Elsheery; Mahmoud Mohy Elhaig; Matthhew C Riley; Melissa A Kennedy (Journal of Infection in Developing Countries)
Introduction: Bovine viral diarrhea (BVD) is one of the most economically significant diseases in the bovine industry causing losses due to diarrhea, reproductive disorders, immunosuppression and mortalities. The aim of our investigation was to detect and subtype BVDV from calves on two dairy cattle and two buffalo farms in Ismailia province, Egypt as an indicator of BVDV infection status in the province. Methodology: A total of 298 blood samples were collected and tested using an optimized one-step, real-time multiplex Taqman-based RT-PCR. All the positive samples by the multiplex real-time RT-PCR were tested using conventional RT-PCR to amplify multiple areas of the genome for further phylogenetic analysis and subtyping. Results: Thirty one (10.4%) of the tested samples were positive for BVDV-1. Only three samples, all from a single dairy cattle farm, had enough viral RNA to be amplified by RT-PCR. The PCR products were sequenced and phylogenetic analysis revealed detection of BVDV-1b. The detected strain is closely related to worldwide BVDV-1b strains, making it difficult to trace its origin. Nucleotide and amino acid alignments of the E2 glycoprotein region of the detected strain with other BVDV-1b strains showed high divergence, with identity ranging from 81.3% to 93.6% and 85.3% to 93.6%, respectively. Conclusion: To our knowledge, this is the first report describing the circulation of BVDV-1b in Egyptian dairy cattle populations.